TASTE MASKING OF DONEPEZIL HYDROCHLORIDE USING DIFFERENT ION EXCHANGE RESINS- A COMPARATIVE STUDY - Zainuddin, Rana; Kulkarni, Alpana; Chavan, Hemant; Patil, Gunjan; Zaheer, Zahid; Sangshetti, Jaiprakash N. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
Taste mainly depends on the physiology, sensitivity and structure of taste buds. It is an important parameter in administering drugs orally. Bitter taste is a major limitation to patient compliance. Donepezil hydrochloride (DH) is a bitter drug used in Alzheimers disease. Amongst the many techniques for taste masking, using ion exchange resins has been extensively reported. The technique of forming tasteless complexes with bitter drugs involves selection of most appropriate exchanger and optimization of complexing ratio. The aim of the present work was to select the best cationic exchanger amongst Indion 414, Indion 234 and Indion 214. All parameters were optimized to produce drug-loaded tasteless complexes. Complexation was carried out using batch process prior to which, acid-alkali activation was performed to remove adsorbed impurities from the resin bed surface and hence improve loading efficiency. UV-spectrophotometric method was used to determine percent drug loading. The molecular properties of drug resin complexes were studied using Fourier Transform Infra-red Spectroscopy, Differential Scanning Calorimetry and Xray Powder Diffraction which confirmed complexation. Indion 414 was found to give highest drug loading and minimal drug was released from the complex at salivary pH. Key words: Donepezil HCl, Ion exchange resins, Molecular properties, Taste masking